(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The paper aims at investigating the current status of Afghan women’s human rights from the perspective of constitutional and comparative public law in light of the debate on minority women’s condition in multicultural and multiethnic legal systems. Moving beyond the analysis of the Afghan legal system and hinging on selected statistics on Afghanistan’s ethnically diverse composition, the first part of the paper examines Afghan’s women condition following the coming into force of the 2004 Constitution by interlacing the constitutional provisions with the existing rules of Personal and Customary Law. The second part of the paper goes on by comparing the Afghan legal system with selected European and extra-European Countries featured by systems of law, that similarly to Afghanistan rely on a mixture of State Laws, Personal, and Customary Laws to highlight the extent to which these systems affect women’s human rights and, especially, those of minority women